A comparative study on the removal of an emerging contaminant Mefenamic acid from aqueous media by various advanced oxidation methods. (2021) - Deepa, R.; Madhu, G.; Thomas, Roy M.
Abstract: The efficacy of different advanced oxidation methods such as UV, UV/ H2 O2, Fenton and Photo Fenton in removing an emerging contaminant, Mefenamic acid from aqueous solution has been compared in this work. The effect of three major operating parameters such as pH, concentration of oxidant and catalyst on the degradation of the compound was analysed. The removal of the compound occurred slowly in the case of direct photolysis using UVA radiation and only 40% removal could be achieved after one-hour exposure to UV radiation. Fenton process could achieve an improved removal efficiency of 80 percent at 0.02 mM Fe 2+ and 8 mM H2 O2 concentration in acidic pH range. The removal efficiency improved further in UV/ H2 O2 process and 94 percent was noticed in 30 min with 1 mM H2 O2 concentration. Photo Fenton process resulted in the maximum removal efficiency of 98% within 20 min in acidic pH range. The fastest and the high removal of Mefenamic acid was obtained in the case of Photo Fenton process, among the four advanced oxidation processes studied.